Food Safety Training Needs at Evacuation Shelters Operated by Faith-Based Organizations - Kwon, Junehee; Zottarrelli, Lisa; Kwon, Sockju; Lee, Yee Ming; Ryu, Dojn (My University, 2016)
The authors conducted a survey to identify food safety training needs at evacuation shelters operated by faith-based organizations (FBOs) in four hurricane-prone states. Five thousand randomly selected FBO leaders were asked questions about their food safety attitudes and food handling practices at evacuation shelters. Descriptive statistics and multivariate analysis of variance were calculated to summarize and prioritize the responses. Results from 138 leaders revealed that on average, 590 ± 4,787 evacuees were served for 36 ± 72 days at FBO-operated shelters. Only 19.6% felt they were well prepared for the shelter. Only 5.8% had professional food preparation staff and many accepted hot (47.8%) and cold (37%) prepared food donations. Some lacked adequate refrigerator (18.8%) or freezer (16.7%) spaces, but 40% kept hot food leftovers for later use. The majority did not provide food safety training before opening the shelters (73.2%), yet 76.9% said they will provide food to evacuation shelters again. The results show a need for food safety training and specific strategies for training at FBOs.
Citation: Kwon, J., Zottarelli, L., Kwon, S., Lee, Y. M., & Ryu, D. (2013). Food safety training needs at evacuation shelters operated by faith-based organizations. Journal of Environmental Health, 76(2), 14-21.